Islamisasi Etnik Tionghoa di Kota Medan, 1961-1998 - Sabrina, Annisa; Asari, Hasan; Zuhriah, Zuhriah (Mahesa Research Center (PT. Mahesa Global Publishing), 2020)
This article discusses the Islamization of ethnic Chinese in Medan City, 1961-1998. The entry of ethnic Chinese in Medan City has a different time span and two waves have occurred. The first wave began when the Chinese trade fleet came to visit the port and conducted trade relations, then the second wave when the Dutch needed workers engaged in plantations. In this study using historical methods. The procedures that have been implemented in this study are heuristics (collection of sources), verification (historical criticism), interpretation, and historiography. The Islamization of Chinese ethnics in the city of Medan is due to the belief that occurs in someone who wants to embrace Islam, not because of coercion that must be faced. This belief is attended by a special interest in getting to know Islamic teachings after comparing them with the teachings of other religions. In addition, because of the calm and comfort that is felt after embracing Islam.